1987
DOI: 10.1111/j.1600-9657.1987.tb00614.x
|View full text |Cite
|
Sign up to set email alerts
|

Root form and canal anatomy of maxillary first premolars in a southern Chinese population

Abstract: Racial differences in dental crown morphology have long been recognized, but the frequency of genetically determined variations in root form and canal anatomy has not been established. Features of root and root canal morphology that occur at particularly high frequency in Mongoloid populations have not been systematically documented, and the implications that such features may have upon clinical endodontics have not been fully reported. In this study 100 maxillary first premolars extracted from Hong Kong Chine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
50
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 14 publications
8
50
6
Order By: Relevance
“…There are varying reports from similar Asian studies. Walker and Loh in separate studies done in south-Chinese populations have found that 60% and 50% of their sample had single root [9,10]. Similarly a CBCT (Cone-Beam Computed Tomography) study done by Tian et al in Chinese population has found that 66% of the maxillary first premolars had single root [14][15][16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are varying reports from similar Asian studies. Walker and Loh in separate studies done in south-Chinese populations have found that 60% and 50% of their sample had single root [9,10]. Similarly a CBCT (Cone-Beam Computed Tomography) study done by Tian et al in Chinese population has found that 66% of the maxillary first premolars had single root [14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Maxillary first premolars are usually thought to have two roots. However there are numerous racial differences on the root form, number of root and root canal system [7][8][9][10]. Extraction of maxillary first premolar might be difficult, especially when it has two separate roots.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have shown different trends in the shape and number of roots and canals among different populations (Walker, 1987(Walker, , 1988aManning, 1990a;Gulabivala et al, 2001Gulabivala et al, , 2002. These variations appear to be genetically determined (Tratman, 1938(Tratman, , 1950Sperber, 1967;Somogyi-Csimazia and Simmons, 1971;Curzon, 1974;Trope et al, 1986;Chaparro et al, 1999;Cleghorn et al, 2007) and are important in tracing the racial origins of populations.…”
Section: Introductionmentioning
confidence: 99%
“…The study of root and canal anatomy has clinical (Vertucci, 1984;Çaliskan et al, 1995;Sert and Bayiril, 2004) and anthropological (Tratman, 1950;Dahlberg, 1965;Walker 1987Walker , 1988aPeiris et al, 2007) significance. A number of studies have shown different trends in the shape and number of roots and canals among different populations (Walker, 1987(Walker, , 1988aManning, 1990a;Gulabivala et al, 2001Gulabivala et al, , 2002.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a thorough knowledge of the morphology of the teeth and an expectation of their likely variations is paramount to minimize endodontic failure caused by incomplete debridement and obturation (1). Previous studies have shown different trends in the shape and number of roots and canals among populations (2)(3)(4)(5)(6), which appear to be genetically determined (7)(8)(9) and are important for tracing the racial origins of populations.…”
Section: Introductionmentioning
confidence: 99%